Evaluating the Safety of West Nile Virus Immunity During Congenital Zika Virus Infection in Mice - Acklin, Joshua A.; Cattle, Javier D.; Moss, Arianna S.; Brown, Julia A.; Foster, Gregory A.; Krysztof, David; Stramer, Susan L.; Lim, Jean K. (Frontiers in Immunology, 2021)
Antibody-dependent enhancement (ADE) is a phenomenon that occurs when cross-reactive antibodies generated from a previous flaviviral infection increase the pathogenesis of a related virus. Zika virus (ZIKV) is most recent flavivirus introduced to the Western Hemisphere and has become a significant public health threat due to the unanticipated impact on the developing fetus. West Nile virus (WNV) is the primary flavivirus that circulates in North America, and we and others have shown that antibodies against WNV are cross-reactive to ZIKV. Thus, there is concern that WNV immunity could increase the risk of severe ZIKV infection, particularly during pregnancy. In this study, we examined the extent to which WNV antibodies could impact ZIKV pathogenesis in a murine pregnancy model. To test this, we passively transferred WNV antibodies into pregnant Stat2-/- mice on E6.5 prior to infection with ZIKV. Evaluation of pregnant dams showed weight loss following ZIKV infection; however, no differences in maternal weights or viral loads in the maternal brain, spleen, or spinal cord were observed in the presence of WNV antibodies. Resorption rates, and other fetal parameters, including fetal and placental size, were similarly unaffected. Further, the presence of WNV antibodies did not significantly alter the viral load or the inflammatory response in the placenta or the fetus in response to ZIKV. Our data suggest that pre-existing WNV immunity may not significantly impact the pathogenesis of ZIKV infection during pregnancy. Our findings are promising for the safety of implementing WNV vaccines in the continental US.